KEAMANAN DATA DALAM SISTEM MANAJEMEN PENDIDIKAN BERBASIS TEKNOLOGI DI PEKANBARU - Monia, Fenny Ayu; Hanafi, Imam; Rahmi, Azvi; Fadilah, Isna (STKIP Pesisir Selatan, 2025)
This study aims to evaluate the level of data security, identify risks, and formulate solutions to enhance security in technology-based educational management systems in junior high schools (SMP) in Pekanbaru City. A quantitative approach using survey methods was employed to collect data from 50 schools selected through stratified random sampling. The primary instruments used were questionnaires and interviews, focusing on aspects such as authentication, data backups, and security training. The findings revealed that public schools outperformed private schools in implementing security measures, such as two-factor authentication (80% vs. 40%) and daily data backups (55% vs. 15%). Key risks identified included low backup frequency, insufficient adoption of security technologies, and users' limited awareness of data security threats. Proposed solutions include adopting advanced security technologies, regular training programs, comprehensive data management policies, annual evaluations, and government support. These measures aim to enhance student data protection, operational efficiency, and public trust in technology-based educational systems. This study provides significant contributions to the development of comprehensive and sustainable data security strategies in the education sector.